Sistem Klasifikasi Telur Ayam Fertil dan Infertil Menggunakan Fitur Tekstur Dan Metode K-Nearest Neighbor Berbasis Raspberry - Pandy Aldrige Simanungkalit; Hurriyatul Fitriyah; Eko Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Fertile chicken eggs are eggs that fertilized by a male and have potential to hatch while infertile eggs are eggs that not fertilized by a male. In chicken hatching management infertile eggs need to be removed from hatching machine so that they do not rot and explode in hatching machine. The removing process of infertile eggs from hatching machine doing by candling the eggs using a flashlight or lamp placed behind the eggs. In hatching industry with a large capacity doing this process is very tiring for the eyes because it requires high concentration and accuracy so this affects the consistency and accuracy of the observation results, therefor a system that classify fertile and infertile eggs constantly is needed. This study design classification system for fertile and infertile eggs based on Computer Vision with texture feature extracted using Gray Level Co-Occurrence Matrix method and classified using K-Nearest Neighbor method. To support the memory requirements for image processing the system is run on a raspberry pi device. The results of analysis and testing using K-Fold Cross Validation of Gray Level Co-Occurrence Matrix feature extraction show that the best feature combination is dissimilarity-correlation and Classification results using K-Nearest Neighbor show an accuracy rate of 93,33% on the number of neighbor K=7 and 9.